Immigration and status exchange in Australia and the United States - Kate H. Choi; Marta Tienda; Deborah A. Cobb-Clark; Mathias Sinning (Institute for the Study of Labor (IZA), 2011)
The claim that marriage is a venue for status exchange of achieved traits, like education, and ascribed attributes, notably race and ethnic membership, has regained traction in the social stratification literature. Most studies that consider status exchanges ignore birthplace as a social boundary for status exchanges via couple formation. This paper evaluates the status exchange hypothesis for Australia and the United States, two Anglophone nations with long immigration traditions whose admission regimes place different emphases on skills. A log-linear analysis reveals evidence of status exchange in the United States among immigrants with lower levels of education and mixed nativity couples with foreign-born husbands. Partly because Australian educational boundaries are less sharply demarcated at the postsecondary level, we find is weaker evidence for the status exchange hypothesis. Australian status exchanges across nativity boundaries usually involve marriages between immigrant spouses with a postsecondary credential below a college degree and native-born high school graduates.
urn:nbn:de:101:1-201106202031
Keywords: F22; I24; 330; status exchange; immigration; educational assortative mating; Sozialer Status; Migranten; Ehe; Bildungsniveau; Australien; USA